Physiological and behavioral responses of sows under different shading structures in a tropical free-range system - Nascimento, Sheila Tavares; do Nascimento Mós, João Victor; Teixeira, Bruno Emanoel; Passos, Bárbara Martins; Murata, Luci Sayori; dos Santos, Vinícius Machado; de Oliveira, Evandro Menezes; Maia, Alex Sandro Campos [UNESP]; Neto, Antonio José Steidle (Springer Nature, 2025)
This study aimed to investigate the effect of different shade structures on the physiological and behavioral responses of sows in free-range systems in a tropical climate. Six non-pregnant DanBred sows were studied from November to December 2019 at the University of Brasília, Federal District, Brazil. The sows were distributed in a double 3 × 3 Latin square design in six paddocks, each containing one of the three artificial shade treatments, so that each artificial shade treatment was present in two paddocks. In each evaluated paddock there was a Caryocar Brasiliense, a native tree from Brazilian Cerrado with 6.0 m mean height, as well as a mud pool, to allow the sows to perform natural behaviors. Treatments included shade provided by a black net (blocking 80% of radiation), shade provided by a heat-reflective net (blocking 80% of radiation), and both nets combined. Black globe, dry bulb, and wet bulb temperatures, relative humidity, and wind speed were measured at 1 min intervals between 8:00 and 16:00 h during 18 non-consecutive days. For behavioral observation, an ethogram was developed describing sows’ site preferences, body posture and activities of interest. Vaginal and body surface temperatures were measured every 1 min and respiratory rate every 20 min. Micrometeorological and physiological data were analyzed using SAS software. The means were compared using Tukey’s test with a significance level of 5%. Behavioral data were subjected to frequency analysis and chi-square tests at the 5% significance level. Shade treatments affected (p < 0.05) all meteorological, behavioral, and physiological variables. The combined use of heat-reflective and black nets provided the best meteorological results, being more frequently used by sows than tree shade. However, shade type did not physiologically influence internal body temperature, surface temperature, or respiratory rate, demonstrating the importance of behavioral expression for thermoregulation.
Keywords: Shade nets; Solar radiation; Swine; Thermal comfort; Thermoregulation